Perceptions of death and memory transmission among residents of Hiroshima and Nagasaki, Japan: A qualitative study - Monte-Angel Richardson; Carly Parmer (Public Library of Science (PLoS), 2023)
The understanding and materialization of grief and loss in a community are contingent upon cultural norms, historical processes, and dominant political narratives. The processes of public mourning create a localized memory of the deceased which contributes to a collective narrative formation around loss. When death is made public, politicized, or collectively grieved, there exists great momentum for enacting policy change through restorative justice practices. This momentum for resistance is amplified when collective grieving takes place following political or mass deaths. The present study aims to develop a holistic understanding of mourning and memorialization practices as they are locally enacted in Hiroshima and Nagasaki, Japan. These two cities were chosen based on their shared history of mass violence and their diverging cultural customs of mourning. Twelve qualitative interviews were conducted with residents of both cities. The purpose of the interviews was to gain insight to how Hiroshima and Nagasaki residents make meaning out of loss and public memorialization. Narrative interviews based on the Miyabayashi Grief Measurement (MG) allowed participants to explain and reflect on the links between their public and individual mourning practices. Themes identified in the interviews include (1) a routine and automatic engagement with grief rituals specific to Japanese culture; (2) connection and gratitude towards ancestors; (3) methods of engaging with memorial sites to transmit personal memories of the deceased; (4) a sense of duty in passing on the first-hand accounts of survivors of the atomic bombing; (5) recalling memories of the deceased when making decisions; and, (6) transmitting memories of loss in a way that is celebratory and joyous. These results ask us to look past simplified depictions of cultural grief and consider the individual elements that may impact a person's remembrance and memory transmission within societies.